If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 23 = 2x + 8 + x Reorder the terms: 23 = 8 + 2x + x Combine like terms: 2x + x = 3x 23 = 8 + 3x Solving 23 = 8 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 23 + -3x = 8 + 3x + -3x Combine like terms: 3x + -3x = 0 23 + -3x = 8 + 0 23 + -3x = 8 Add '-23' to each side of the equation. 23 + -23 + -3x = 8 + -23 Combine like terms: 23 + -23 = 0 0 + -3x = 8 + -23 -3x = 8 + -23 Combine like terms: 8 + -23 = -15 -3x = -15 Divide each side by '-3'. x = 5 Simplifying x = 5
| (x-3)2+5x=(x+2)2-5 | | Q=5aP^2+9bP^3 | | 4y-3+y+37=8y+40-6y | | 3a-2b-c=0 | | 6x^2y^3+10x^2y^2k-30x^3y^2-2xy^3= | | 13+9x=7x | | 11/3*x=2/5 | | 5f-15=f+-10 | | 8a-a=10 | | 5/7x=3/5 | | 4/7*x=3/21 | | 3(4+5a)=30 | | 2x(x+5)=3(x+5) | | 2x+1y-5=5 | | -4a=3b | | 14q=98 | | 4x^2/0.38-x=0.671 | | -8x-8=34-x | | 5y-3/4+5=13 | | -2(8+4x)=(8+3x) | | 2x^2-13x+27=0 | | m(6m+3)= | | 10x^2+35x-75=0 | | 4(7-5)= | | 3m+-6=9 | | S+4=-6 | | U=55(6)+217 | | U=55n+217 | | 12=0.75x+1.35x | | 23-5y=23+5y | | -50t^2+100t=0 | | 16x+48= |